Solid‐Solution Coordination Polymers as Precursors for ZnxCd1–xS/C Composite Nanowires. Issue 18 (11th May 2017) - Tajima, Shinya; Kuroshima, Yoshiki; Katayama, Tetsuro; Tamai, Naoto; Sada, Kazuki; Hirai, Kenji
Abstract : The development of synthetic routes to nanomaterials has been motivated by their potential applications in electronics, optics, and catalytic reactions. Solution‐based synthesis has relied on organic stabilizers to regulate the crystal growth. Despite the beneficial effect on crystal growth, organic stabilizers attached to the resulting particles reduce the accessibility of reactants and inhibit charge transport, resulting in a lower catalytic activity than expected. In this work we have demonstrated that coordination polymers (CPs) can be used as precursors for photocatalysts without stabilizers. The pyrolysis of CP nanowires of [Cd(l ‐cysteinate)] n gave CdS/C nanowires (CdS/C‐NWs) that exhibit photocatalytic activity for hydrogen generation superior to CdS nanowires with organic stabilizers (CdS/stb‐NWs). Transient absorption spectroscopy showed that CdS/C‐NWs provide an active surfaces to facilitate catalytic reactions associated with electron migration. Moreover, Zn‐doped CdS nanowires (ZnxCd1‐xS/C‐NWs) obtained by the pyrolysis of CPs exhibited higher photocatalytic activity than nondoped CdS/C‐NWs. The improvement in photocatalytic activity is attributable to the prolonged lifetime of photoexcited electrons. The pyrolysis of CPs provides a facile means to design nanocomposites that realize efficient catalytic reactions associated with facile charge transfer. Abstract : We demonstrate that coordination polymers can be used as precursors for photocatalysts without stabilizers. The pyrolysis of coordination polymer nanowires gives CdS/C or Zn‐doped CdS/C nanowires that exhibit photocatalytic activities for hydrogen generation superior to CdS nanowires with organic stabilizers.